2014
DOI: 10.1159/000362547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advanced Hearing Aid Technology on Speech Understanding for Older Listeners with Mild to Moderate, Adult-Onset, Sensorineural Hearing Loss

Abstract: Background: Hearing loss is one of the most common chronic health conditions of older people. Hearing aids are the customary treatment and they improve quality of life in older adults. Even so, relatively few older adults with uncomplicated, mild to moderate, adult-onset, sensorineural hearing loss use hearing aids. One reason for this is a belief that hearing aids do not provide sufficient value to justify their expense. Although modern hearing aids are available at several price points, there is minimal evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
4
46
1
Order By: Relevance
“…This is consistent with a value of Cohen’s d = 0.5. As we have noted previously (Cox, Johnson, & Xu, 2014), a medium effect size would result in about 20% of individuals who wear premium-feature hearing aids performing above the distribution for persons wearing basic-feature devices. Also, a difference equal to a medium effect would create a probability of about .64 that an individual would perform better with premium-feature hearing aids than with basic-feature hearing aids (keep in mind that with a zero effect, this probability would be .5) (Grissom, 1994).…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…This is consistent with a value of Cohen’s d = 0.5. As we have noted previously (Cox, Johnson, & Xu, 2014), a medium effect size would result in about 20% of individuals who wear premium-feature hearing aids performing above the distribution for persons wearing basic-feature devices. Also, a difference equal to a medium effect would create a probability of about .64 that an individual would perform better with premium-feature hearing aids than with basic-feature hearing aids (keep in mind that with a zero effect, this probability would be .5) (Grissom, 1994).…”
Section: Methodssupporting
confidence: 53%
“…Quality of life outcomes for 25 of these participants were presented in Cox et al (2014). The present article expands on those data with the additional power provided by 20 more participants as well as presenting previously unreported outcomes reflecting the patient’s perspective.…”
Section: Methodsmentioning
confidence: 95%
“…A detailed description of participant demographics is provided in Cox et al (2016). Speech-understanding outcomes for the first 25 of these participants were presented in Cox et al (2014). The present article expands on those data with the additional power provided by 20 more participants and presents previously unreported outcomes in the domain of listening effort.…”
Section: Methodsmentioning
confidence: 96%
“…The rationales for the first four features listed in Table 1 and a brief review of the published independent research about their effectiveness in the domain of speech understanding can be found in Cox et al 2014. At the time of that writing there was a lack of independent literature indicating any real world advantages of the four premium features over the basic versions of those features in speech understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The pricing structure for "high-end" versus "basic" hearing aids is of dubious benefit, however, with some literature suggesting little functional difference to justify the price disparity between these 2 levels of technology (generally several thousand dollars). 45 A second reason for the high cost of hearing aids is that they are obtained by audiologists at a high wholesale cost as a result of the low volume of hearing aid sales (ϳ20 units/month 43 ) for most providers. By contrast, the wholesale cost of a pair of mid-tier hearing aids when purchased by large-volume providers such as the Veterans Administration in the United States and the National Health Service in the United Kingdom is generally less than $300.…”
Section: Cost Of Hearing Carementioning
confidence: 99%